2016
DOI: 10.1016/j.fuproc.2016.01.029
|View full text |Cite
|
Sign up to set email alerts
|

1-hexene autoignition control by prior reaction with ozone

Abstract: The autoignition timing of 1-hexene was controlled in a Homogeneous Charge Compression Ignition (HCCI) engine by reacting the fuel with ozone-containing air prior to its combustion. The experiments were conducted in a single cylinder research engine instrumented with a cylinder pressure sensor. The fuel was chemically characterised using Nuclear Magnetic Resonance (NMR) spectroscopy before and after its reaction with ozone. The NMR analyses showed that this preliminary reaction produced several oxygenated prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…O 3 facilitating 1-hexene conversion under typically inhibitory combustion conditions is consistent with the results of Schonborn et al 68 who reported the ignition improvement of an HCCI combustion engine. The influence of O 3 on the NTC has also been recently reported for several O 3 -initiated alkane oxidation systems, 24,25 but temperature investigations for alkenes between 300 and 600 K, enabling the observation of atmospheric/combustion chemistry transitions, were so far limited to ethylene 27,29 and butene.…”
Section: ■ Conclusionsupporting
confidence: 91%
“…O 3 facilitating 1-hexene conversion under typically inhibitory combustion conditions is consistent with the results of Schonborn et al 68 who reported the ignition improvement of an HCCI combustion engine. The influence of O 3 on the NTC has also been recently reported for several O 3 -initiated alkane oxidation systems, 24,25 but temperature investigations for alkenes between 300 and 600 K, enabling the observation of atmospheric/combustion chemistry transitions, were so far limited to ethylene 27,29 and butene.…”
Section: ■ Conclusionsupporting
confidence: 91%
“…those that require reduced durations of ignition delay or variable control of the ignition timing. 116,117 Declaration of conflicting interests…”
Section: The Presence Of Aromatic Molecules In Binary Fuelmentioning
confidence: 99%
“…In the literature, 1-hexene (C 6 H 12 ) is often proposed as a representative alkene component in gasoline surrogate fuels. However, there is only one study on the reactions of this fuel with O 3 under combustion-relevant conditions. This was performed in a homogeneous charge compression ignition (HCCI) engine by reacting a variable fuel portion with O 3 -containing air by Schönborn et al . These measurements indicate an increase in pressure and heat release in the presence of O 3 , as well as earlier ignition.…”
Section: Introductionmentioning
confidence: 99%
“…13−15 However, there is only one study on the reactions of this fuel with O 3 under combustion-relevant conditions. This was performed in a homogeneous charge compression ignition (HCCI) engine by reacting a variable fuel portion with O 3 -containing air by Schonborn et al 16 These measurements indicate an increase in pressure and heat release in the presence of O 3 , as well as earlier ignition. There was also a notable decrease in particle emissions and an increase in combustion efficiency under elevated pressure and temperature conditions.…”
Section: ■ Introductionmentioning
confidence: 99%